Sustainability Reporting and Assurance: A New Challenge for the Audit Profession in Europe - Darko DACHEVSKI; Barry ACKERS (Audit Financiar)
This study investigates the familiarity of auditors with sustainability reporting and assurance concepts across different sizes of audit firms in Europe. Utilizing extensive literature and quantitative surveys deployed at auditors and audit firms in Europe, the research reveals that auditors associated with international audit networks and larger audit firms demonstrate a greater familiarity with sustainability reporting and assurance concepts and practices compared to auditors associated with smaller, local audit firms. The findings suggest that this familiarity gap stems from the predominant involvement of larger audit firms in providing sustainability reporting services and assurance for their clients. To narrow this familiarity gap, the study proposes collaborative efforts involving academia and professional audit associations to deliver training on sustainability reporting and assurance concepts and practices. Recognizing auditor proficiency and knowledge as crucial factors in ensuring the quality of assurance services in this domain, the study emphasizes the importance of enhancing external auditors’ competencies in sustainability reporting and assurance. Furthermore, the study advocates for the implementation of stringent regulations by national authorities to secure the market for sustainability reporting and assurance, aligning with previous scholarly calls for clearer regulatory frameworks in this sphere. However, the study underscores the need for further research to assess the impact of such regulations on the professional market for sustainability reporting and assurance. Implications for the European audience: For the European audience, the study underscores the significance of collaborative training initiatives led by academia and professional audit associations to equip external auditors with the requisite skills necessary for delivering assurance services on sustainability reporting of satisfactory quality. The study recommends the adoption of stringent regulatory frameworks to safeguard the sustainability reporting and assurance market. These measures are essential for ensuring credibility and reliability in sustainability reporting practices.